Tissue/organ-derived bioink formulation for 3D bioprinting. Issue 1 (27th February 2019) - Chameettachal, Shibu; Sasikumar, Shyama; Sethi, Soumya; Sriya, Yeleswarapu; Pati, Falguni
Tissue/organ-derived bioink formulations open up new avenues in 3D bioprinting research with the potential to create functional tissue or organs. Printing of tissue construct largely depends on material properties, as it needs to be fabricated in an aqueous environment while encapsulating living cells. The decellularized extracellular matrix bioinks proved to be a potential option for functional tissue development in vivo and as an alternative to chemically cross-linked bioinks. However, certain limitations such as printability and limited mechanical strength need to be addressed for enhancing their widespread applications. By drawing knowledge from the existing literature, emphasis has been given in this review to the development of decellularized extracellular matrix bioinks and their applications in printing functional tissue constructs.